Fat acid extraction from Naviculla Salinicola and Chlorella Vulgaris with simple laboratory tools - surani hendra (Labor Dasar dan Sentral Universitas Andalas, 2020)
Energy alternatives are starting to get attention due to the depletion of petroleum sources as the current fuel. One of them is biodiesel. Microalgae has the potential to produce fat that can be proceed into biodiesel. This study aims to find the shaking time and the suitable solvent with the extraction of microalgaes, namely Naviculla Salinicola and Chlorella Vulgaris fatty acids with various solvents, namely hexane, methanol and chloroform. Each microalgae can affect different cell walls that resulting in different extraction materials. The results showed that fatty acids Chlorella Vulgaris and Naviculla Salinicola were extracted the most with hexane. The fat content extracted from Chlorella Vulgaris with three solvents were 10.56% for hexane, 6.79% for methanol and 5.99% for chloroform. For the extraction of Naviculla salinicola with hexane solvent yielded 4.37% fat, while with choloroform was 2.99% and with methanol was 2.48%. The increase in processing time resulted in an increase in the equivalent of fat extraction in both types of microalgae with the highest one was obtained at the five-hour shaking time.